2018
DOI: 10.4067/s0717-95022018000200425
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Variations in Relation to the Origin of the Musculocutaneous Nerve: Absence and Non-Perforation of the Coracobrachialis Muscle. Anatomical Study and Clinical Significance

Abstract: SUMMARY:The most frequent anatomic variations of the musculocutaneous nerve could be divided in two main groups: communicating branches with the median nerve and variations in relation to the origin, which in turn can be subdivided into absence of the nerve and non-perforation of the coracobrachialis muscle. Unusual clinical symptoms and/or unusual physical examination in patients with motor disorders, could be explained by anatomic variations of the musculocutaneous nerve. A total of 106 arms were evaluated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Α total of 126 studies were identified, 28 of which were assessed as full-text articles (Figure 1). Out of these, 23 manuscripts (1,2,15,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) were used for estimation of the MCN's typical course, 10 (6, 12, 15, 17, 27, 34, 36, 39-41) for calculation of the distance between the CP and the entrance point of the MCN into the CB, and 7 (2,6,12,15,17,36,40), for computation of the distance between the CP and the point of origin of the proximal branches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Α total of 126 studies were identified, 28 of which were assessed as full-text articles (Figure 1). Out of these, 23 manuscripts (1,2,15,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) were used for estimation of the MCN's typical course, 10 (6, 12, 15, 17, 27, 34, 36, 39-41) for calculation of the distance between the CP and the entrance point of the MCN into the CB, and 7 (2,6,12,15,17,36,40), for computation of the distance between the CP and the point of origin of the proximal branches.…”
Section: Resultsmentioning
confidence: 99%
“…Developmentally, the MCN derives late during arm development. Disruption in BP differentiation may lead to the MCN's absence (24,42,43). In these circumstances, the MCN fibers are fused with the median nerve (MN) in a common trunk, responsible for the anterior arm compartment's motor innervation (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscles' formation is completed before nerves' formation. Thus, "the nerve follows the muscle", and as a result, a developmental problem in muscle differentiation leads to the abnormal innervation [4,15,28]. After the formation of the muscles and nerves supplying the entire limb, begin to form a plexus, in the form of loops, between nerve bers, and in this way the MCN originates from the MN [3], late during arm development.…”
Section: Discussionmentioning
confidence: 99%
“…After the formation of the muscles and nerves supplying the entire limb, begin to form a plexus, in the form of loops, between nerve bers, and in this way the MCN originates from the MN [3], late during arm development. Disruption in the brachial plexus differentiation may lead to the MCN absence [4,15,28].…”
Section: Discussionmentioning
confidence: 99%